2022
DOI: 10.1093/mnras/stac1840
|View full text |Cite
|
Sign up to set email alerts
|

Blanco DECam Bulge Survey (BDBS) IV: Metallicity distributions and bulge structure from 2.6 million red clump stars

Abstract: We present photometric metallicity measurements for a sample of 2.6 million bulge red clump stars extracted from the Blanco DECam Bulge Survey (BDBS). Similar to previous studies, we find that the bulge exhibits a strong vertical metallicity gradient, and that at least two peaks in the metallicity distribution functions appear at b < −5○. We can discern a metal-poor ([Fe/H] ∼ −0.3) and metal-rich ([Fe/H] ∼ +0.2) abundance distribution that each show clear systematic trends with latitude, and may be best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 165 publications
0
11
0
Order By: Relevance
“…The Galactic bulge is the sole spheroid where individual stars can be observed and for this reason is a formidable laboratory to study the processes that drive the formation of galaxy bulges. Unfortunately, because of observational limitations mainly related to the large extinction and stellar density in this direction of the sky, it still remains one of the most inaccessible regions of the Milky Way, and its structure, formation, and evolution are still subjects of intense debate in the literature (see, for example, Ness et al 2013;Rich 2013;Origlia 2014;Zoccali & Valenti 2016;Johnson et al 2022;Marchetti et al 2022). In this respect the investigation of the globular clusters (GCs) orbiting the bulge is a key tool to trace the bulge properties in terms of kinematics, chemical abundances, and age (Bica et al 2006;Valenti et al 2007Valenti et al , 2010; Barbuy et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The Galactic bulge is the sole spheroid where individual stars can be observed and for this reason is a formidable laboratory to study the processes that drive the formation of galaxy bulges. Unfortunately, because of observational limitations mainly related to the large extinction and stellar density in this direction of the sky, it still remains one of the most inaccessible regions of the Milky Way, and its structure, formation, and evolution are still subjects of intense debate in the literature (see, for example, Ness et al 2013;Rich 2013;Origlia 2014;Zoccali & Valenti 2016;Johnson et al 2022;Marchetti et al 2022). In this respect the investigation of the globular clusters (GCs) orbiting the bulge is a key tool to trace the bulge properties in terms of kinematics, chemical abundances, and age (Bica et al 2006;Valenti et al 2007Valenti et al , 2010; Barbuy et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since the Gaia EDR3 parallaxes are insufficient for deriving accurate distances for faint bulge stars, the second set of distances is estimated from a sample of 2.6 million red clump stars described in Johnson et al (2022). The red clump distance map covers sight lines between |l|= ±10°and b < −3°.25 and encompasses a large fraction of the microlensed dwarf sample.…”
Section: A1 Bdbs Photometrymentioning
confidence: 99%
“…Distances are once again provided by Johnson et al (2022) and Simion et al (2017), with extinction uncertainties in the BP and RP filters calculated as described in Appendix A.1. A lack of reliable distance reduces the full crossmatched sample from 17 to 16 targets, while the gold sample includes eight targets.…”
Section: A2 Gaia Photometrymentioning
confidence: 99%
“…The early measurements of Rich (1988), McWilliam & Rich (1994) established that the bulge's metallicity distribution function (MDF) is broad, reaching supersolar metallicities. More recent observations have shown that the MDF is at least bimodal with possible hints of additional peaks (Ness et al 2013;Schultheis et al 2017;Rojas-Arriagada et al 2020;Johnson et al 2022), although this may partly be due to fitting multiple Gaussians to an intrinsically skewed distribution. Spectroscopic surveys such as ARGOS (Freeman et al 2013), GIBS (Zoccali et al 2014), and APOGEE (Majewski et al 2016) have mapped the chemistry across the bulge (e.g., Ness et al 2013;Gonzalez et al 2015;Zoccali et al 2017;Queiroz et al 2021) generally finding that its [Fe/H]-[α/Fe] plane exhibits a single track, with two peaks and a trough between them.…”
Section: Introductionmentioning
confidence: 99%